AN INTERESTING CASE OF CORONARY-CAMERAL FISTULA WITH ANGINA PECTORIS - Lazovic, Dejan M.; Kočica, Mladen; Đurošev, Ivana; Kočica-Karadžić, Milica; Cvetković, Dragan (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Coronary-cameral fistula (CCF) is an anomalous connection between a coronary artery and a cardiac chamber. Most CCFs are discovered incidentally during angiographic evaluation of coronary vascular disorders. We report a case of CCF with angina pectoris.Case report: A 67-year-old woman presented with chest pain and dyspnea upon exertion. Coronary angiography showed atherosclerotic lesions in the two major coronary arteries, but also communication between three arteries and the cavity of the right ventricle (RV) through many small, diffuse fistulas. Angiography also showed a fistula between the proximal left anterior descending artery (LAD) (first septal branch) and the right ventricle, as well as between the proximal right coronary artery (RCA) (acute marginal branch) and the right ventricle. The patient qualified to undergo coronary artery bypass graft surgery (CABG) and surgical closing of the fistulas, which is why we performed, on a beating heart, double vessel revascularization by autovein graft between the ascending aorta and the RCA and between the ascending aorta and the LAD, as well as closing of the fistulas with hemoclips and polypropylene suture, with a teflon pledget.Conclusion: Hemodynamically insignificant fistulas, which are clinically silent and not associated with other abnormal findings, most commonly do not require further treatment. Large, hemodynamically significant  fistulas should be closed by ligation. However, smaller fistulas tend to get larger with age and it is recommended that early elective closure is performed in patients experiencing symptoms or in asymptomatic patients with a continuous murmur or a systolic murmur with an early diastolic component.
Keywords: coronary artery fistulas; coronary angiography